Blumenberg’s Rhetoric - Feger, Sonja; Godart, Simon; Hiller, Daniel Rudy; Küpper, Joachim; Mayfield, D. S.; Niehues-Pröbsting, Heinrich; Trüstedt, Katrin; Waszynski, Alexander; Weber-Steinhaus, Friedrich; Zambon, Nicola (De Gruyter, 2023)
Marking the 50th anniversary of one among this philosopher’s most distinguished pieces, Blumenberg’s Rhetoric proffers a decidedly diversified interaction with the essai polyvalently entitled ‘Anthropological Approach to the Topicality (or Currency, Relevance, even actualitas) of Rhetoric’ ("Anthropologische Annäherung an die Aktualität der Rhetorik"), first published in 1971. Following Blumenberg’s lead, the contributors consider and tackle their topics rhetorically—treating (inter alia) the variegated discourses of Phenomenology and Truthcraft, of Intellectual History and Anthropology, as well as the interplay of methods, from a plurality of viewpoints. The diachronically extensive, disciplinarily diverse essays of this publication—notably in the current lingua franca—will facilitate, and are to conduce to, further scholarship with respect to Blumenberg and the art of rhetoric. With contributions by Sonja Feger, Simon Godart, Joachim Küpper, DS Mayfield, Heinrich Niehues-Pröbsting, Daniel Rudy Hiller, Katrin Trüstedt, Alexander Waszynski, Friedrich Weber-Steinhaus, Nicola Zambon